Mechanical and Durability Properties of Mortars Modified with Combined Polymer and Supplementary Cementitious Materials - Ahmed, Shaikh (American Society of Civil Engineers (ASCE), 2011)
Repair and restoration work of reinforced-concrete (RC) structures is increasing because of the deterioration of aging infrastructures worldwide. Generally, plain mortar and polymer-modified mortar are widely used as repair materials for RC structures. In this study the effect of the combined use of polymers with supplementary cementitious materials (SCMs) on certain mechanical and durability properties (such as compressive and flexural strengths, water absorption, carbonation, and chloride penetration) of modified mortars is evaluated experimentally. The experimental program consists of two parts. In Part I, the effect of SCM slag and silica fume (SF) on the mechanical and durability properties of mortars is evaluated. On the basis of the best performance among different slag and SF contents, Part II of the experimental program is designed, in which the combined effect of polymers and slag/SF on the mechanical and durability properties of modified mortar is evaluated. Results show that the combined slag/SF and polymer-modified mortars (PMMs) exhibited better results than polymer-modified mortar alone. Between the combined polymers and SF/slag-modified mortars, the polymer-modified mortar containing 10% SF exhibited the highest compressive and flexural strengths and the lowest chloride penetration resistance compared to those containing 40% slag. Interestingly, the combined polymer and 40% slag-modified mortars exhibited better performance in water absorptionand carbonation resistance than polymer-modified mortar containing 10% SF.